This article attempts to give an overview of category theory, in so far as it applies to Haskell. To this end, Haskell code will be given alongside the mathematical definitions. Absolute rigour is not followed; in its place, we seek to give the reader an intuitive feel for what the concepts of category theory are and how they relate to Haskell.

## Introduction to categories A simple category, with three objects A, B and C, three identity morphisms $\operatorname {id} _{A}$ , $\operatorname {id} _{B}$ and $\operatorname {id} _{C}$ , and two other morphisms $f:C\to B$ and $g:A\to B$ . The third element (the specification of how to compose the morphisms) is not shown.

A category is, in essence, a simple collection. It has three components:

• A collection of objects.
• A collection of morphisms, each of which ties two objects (a source object and a target object) together. (These are sometimes called arrows, but we avoid that term here as it has other connotations in Haskell.) If f is a morphism with source object C and target object B, we write $f:C\to B$ .
• A notion of composition of these morphisms. If $g:A\to B$ and $f:B\to C$ are two morphisms, they can be composed, resulting in a morphism $f\circ g:A\to C$ .

Lots of things form categories. For example, Set is the category of all sets with morphisms as standard functions and composition being standard function composition. (Category names are often typeset in bold face.) Grp is the category of all groups with morphisms as functions that preserve group operations (the group homomorphisms), i.e. for any two groups, G with operation * and H with operation ·, a function $k:G\to H$ is a morphism in Grp if:

$k(u*v)=k(u)\cdot k(v)$ It may seem that morphisms are always functions, but this needn't be the case. For example, any partial order (P, $\leq$ ) defines a category where the objects are the elements of P, and there is a morphism between any two objects A and B iff $A\leq B$ . Moreover, there are allowed to be multiple morphisms with the same source and target objects; using the Set example, $\sin$ and $\cos$ are both functions with source object $\mathbb {R}$ (the set of real numbers) and target object $[-1,1]$ , but they’re most certainly not the same morphism!

### Category laws

There are three laws that categories need to follow. Firstly, and most simply, the composition of morphisms needs to be associative. Symbolically,

$f\circ (g\circ h)=(f\circ g)\circ h$ Morphisms are applied right to left in Haskell and most commonly in mathematics, so with $f\circ g$ first g is applied, then f.

Secondly, the category needs to be closed under the composition operation. So if $f:B\to C$ and $g:A\to B$ , then there must be some morphism $h:A\to C$ in the category such that $h=f\circ g$ . We can see how this works using the following category:

f and g are both morphisms so we must be able to compose them and get another morphism in the category. So which is the morphism $f\circ g$ ? The only option is $\operatorname {id} _{A}$ . Similarly, we see that $g\circ f=\operatorname {id} _{B}$ .

Lastly, given a category C there needs to be for every object A an identity morphism, $\operatorname {id} _{A}:A\to A$ that is an identity of composition with other morphisms. Put precisely, for every morphism $g:A\to B$ :

$g\circ \operatorname {id} _{A}=\operatorname {id} _{B}\circ g=g$ The main category we'll be concerning ourselves with in this article is Hask, which treats Haskell types as objects and Haskell functions as morphisms and uses (.) for composition: a function f :: A -> B for types A and B is a morphism in Hask. We can check the first and second law easily: we know (.) is an associative function, and clearly, for any f and g, f . g is another function. In Hask, the identity morphism is id, and we have trivially:

id . f = f . id = f

 This isn't an exact translation of the law above, though; we're missing subscripts. The function id in Haskell is polymorphic — it can take many different types for its domain and range, or, in category-speak, can have many different source and target objects. But morphisms in category theory are by definition monomorphic — each morphism has one specific source object and one specific target object (note: monomorphic here is not being used in the category theoretic sense). A polymorphic Haskell function can be made monomorphic by specifying its type (instantiating with a monomorphic type), so it would be more precise if we said that the identity morphism from Hask on a type A is (id :: A -> A). With this in mind, the above law would be rewritten as:

(id :: B -> B) . f = f . (id :: A -> A) = f

However, for simplicity, we will ignore this distinction when the meaning is clear.

Exercises
• As was mentioned, any partial order (P, $\leq$ ) is a category with objects as the elements of P and a morphism between elements a and b iff a $\leq$ b. Which of the above laws guarantees the transitivity of $\leq$ ?
• (Harder.) If we add another morphism to the above example, as illustrated below, it fails to be a category. Why? Hint: think about associativity of the composition operation.

## Functors A functor between two categories, $\mathbf {C}$ and $\mathbf {D}$ . Of note is that the objects A and B both get mapped to the same object in $\mathbf {D}$ , and that therefore g becomes a morphism with the same source and target object (but isn't necessarily an identity), and $\operatorname {id} _{A}$ and $\operatorname {id} _{B}$ become the same morphism. The arrows showing the mapping of objects are shown in a dotted, pale olive. The arrows showing the mapping of morphisms are shown in a dotted, pale blue.

So we have some categories which have objects and morphisms that relate our objects together. The next Big Topic in category theory is the functor, which relates categories together. A functor is essentially a transformation between categories, so given categories C and D, a functor $F:C\to D$ :

• Maps any object A in C to $F(A)$ , in D.
• Maps morphisms $f:A\to B$ in C to $F(f):F(A)\to F(B)$ in D.

One of the canonical examples of a functor is the forgetful functor $\mathbf {Grp} \to \mathbf {Set}$ which maps groups to their underlying sets and group morphisms to the functions which behave the same but are defined on sets instead of groups. Another example is the power set functor $\mathbf {Set} \to \mathbf {Set}$ which maps sets to their power sets and maps functions $f:X\to Y$ to functions ${\mathcal {P}}(X)\to {\mathcal {P}}(Y)$ which take inputs $U\subseteq X$ and return $f(U)$ , the image of U under f, defined by $f(U)=\{\,f(u):u\in U\,\}$ . For any category C, we can define a functor known as the identity functor on C, or $1_{C}:C\to C$ , that just maps objects to themselves and morphisms to themselves. This will turn out to be useful in the monad laws section later on.

Once again there are a few axioms that functors have to obey. Firstly, given an identity morphism $\operatorname {id} _{A}$ on an object A, $F(\operatorname {id} _{A})$ must be the identity morphism on $F(A)$ , i.e.:

$F(\operatorname {id} _{A})=\operatorname {id} _{F(A)}$ Secondly functors must distribute over morphism composition, i.e.

$F(f\circ g)=F(f)\circ F(g)$ Exercises
For the diagram given on the right, check these functor laws.

The Functor typeclass you have probably seen in Haskell does in fact tie in with the categorical notion of a functor. Remember that a functor has two parts: it maps objects in one category to objects in another and morphisms in the first category to morphisms in the second. Functors in Haskell are from Hask to func, where func is the subcategory of Hask defined on just that functor's types. E.g. the list functor goes from Hask to Lst, where Lst is the category containing only list types, that is, [T] for any type T. The morphisms in Lst are functions defined on list types, that is, functions [T] -> [U] for types T, U. How does this tie into the Haskell typeclass Functor? Recall its definition:

class Functor (f :: * -> *) where
fmap :: (a -> b) -> f a -> f b


Let's have a sample instance, too:

instance Functor Maybe where
fmap f (Just x) = Just (f x)
fmap _ Nothing  = Nothing


Here's the key part: the type constructor Maybe takes any type T to a new type, Maybe T. Also, fmap restricted to Maybe types takes a function a -> b to a function Maybe a -> Maybe b. But that's it! We've defined two parts, something that takes objects in Hask to objects in another category (that of Maybe types and functions defined on Maybe types), and something that takes morphisms in Hask to morphisms in this category. So Maybe is a functor.

A useful intuition regarding Haskell functors is that they represent types that can be mapped over. This could be a list or a Maybe, but also more complicated structures like trees. A function that does some mapping could be written using fmap, then any functor structure could be passed into this function. E.g. you could write a generic function that covers all of Data.List.map, Data.Map.map, Data.Array.IArray.amap, and so on.

What about the functor axioms? The polymorphic function id takes the place of $\operatorname {id} _{A}$ for any A, so the first law states:

fmap id = id


With our above intuition in mind, this states that mapping over a structure doing nothing to each element is equivalent to doing nothing overall. Secondly, morphism composition is just (.), so

fmap (f . g) = fmap f . fmap g


This second law is very useful in practice. Picturing the functor as a list or similar container, the right-hand side is a two-pass algorithm: we map over the structure, performing g, then map over it again, performing f. The functor axioms guarantee we can transform this into a single-pass algorithm that performs f . g. This is a process known as fusion.

Exercises
Check the laws for the Maybe and list functors.

### Translating categorical concepts into Haskell

Functors provide a good example of how category theory gets translated into Haskell. The key points to remember are that:

• We work in the category Hask and its subcategories.
• Objects are types.
• Morphisms are functions.
• Things that take a type and return another type are type constructors.
• Things that take a function and return another function are higher-order functions.
• Typeclasses, along with the polymorphism they provide, make a nice way of capturing the fact that in category theory things are often defined over a number of objects at once. unit and join, the two morphisms that must exist for every object for a given monad.

Monads are obviously an extremely important concept in Haskell, and in fact they originally came from category theory. A monad is a special type of functor, from a category to that same category, that supports some additional structure. So, down to definitions. A monad is a functor $M:C\to C$ , along with two morphisms for every object X in C:

• $\operatorname {unit} _{X}^{M}:X\to M(X)$ • $\operatorname {join} _{X}^{M}:M(M(X))\to M(X)$ When the monad under discussion is obvious, we’ll leave out the M superscript for these functions and just talk about $\operatorname {unit} _{X}$ and $\operatorname {join} _{X}$ for some X.

class Functor m => Monad m where
return :: a -> m a
(>>=)  :: m a -> (a -> m b) -> m b


The class constraint of Functor m ensures that we already have the functor structure: a mapping of objects and of morphisms. return is the (polymorphic) analogue to $\operatorname {unit} _{X}$ for any X. But we have a problem. Although return’s type looks quite similar to that of unit; the other function, (>>=), often called bind, bears no resemblance to join. There is however another monad function, join :: Monad m => m (m a) -> m a, that looks quite similar. Indeed, we can recover join and (>>=) from each other:

join :: Monad m => m (m a) -> m a
join x = x >>= id

(>>=) :: Monad m => m a -> (a -> m b) -> m b
x >>= f = join (fmap f x)


So specifying a monad’s return, fmap, and join is equivalent to specifying its return and (>>=). It just turns out that the normal way of defining a monad in category theory is to give unit and join, whereas Haskell programmers like to give return and (>>=). Often, the categorical way makes more sense. Any time you have some kind of structure $M$ and a natural way of taking any object $X$ into $M(X)$ , as well as a way of taking $M(M(X))$ into $M(X)$ , you probably have a monad. We can see this in the following example section.

### Example: the powerset functor is also a monad

The power set functor $P:\mathbf {Set} \to \mathbf {Set}$ described above forms a monad. For any set S you have a $\operatorname {unit} _{S}(x)=\{x\}$ , mapping elements to their singleton set. Note that each of these singleton sets are trivially a subset of S, so $\operatorname {unit} _{S}$ returns elements of the powerset of S, as is required. Also, you can define a function $\operatorname {join} _{S}$ as follows: we receive an input $L\in {\mathcal {P}}({\mathcal {P}}(S))$ . This is:

• A member of the powerset of the powerset of S.
• So a member of the set of all subsets of the set of all subsets of S.
• So a set of subsets of S

We then return the union of these subsets, giving another subset of S. Symbolically,

$\operatorname {join} _{S}(L)=\bigcup L$ .

Hence P is a monad .

In fact, P is almost equivalent to the list monad; with the exception that we're talking lists instead of sets, they're almost the same. Compare:

Power set functor on Set
Function type Definition
Given a set S and a morphism $f:A\to B$ :
$P(f):{\mathcal {P}}(A)\to {\mathcal {P}}(B)$ $(P(f))(S)=\{f(a):a\in S\}$ $\operatorname {unit} _{S}:S\to {\mathcal {P}}(S)$ $\operatorname {unit} _{S}(x)=\{x\}$ $\operatorname {join} _{S}:{\mathcal {P}}({\mathcal {P}}(S))\to {\mathcal {P}}(S)$ $\operatorname {join} _{S}(L)=\bigcup L$ Function type Definition
Given a type T and a function f :: A -> B
fmap f :: [A] -> [B] fmap f xs = [ f a | a <- xs ]
return :: T -> [T] return x = [x]
join :: [[T]] -> [T] join xs = concat xs

## The monad laws and their importance

Just as functors had to obey certain axioms in order to be called functors, monads have a few of their own. We'll first list them, then translate to Haskell, then see why they’re important.

Given a monad $M:C\to C$ and a morphism $f:A\to B$ for $A,B\in C$ ,

1. $\mathrm {join} \circ M(\mathrm {join} )=\mathrm {join} \circ \mathrm {join}$ 2. $\mathrm {join} \circ M(\mathrm {unit} )=\mathrm {join} \circ \mathrm {unit} =\mathrm {id}$ 3. $\mathrm {unit} \circ f=M(f)\circ \mathrm {unit}$ 4. $\mathrm {join} \circ M(M(f))=M(f)\circ \mathrm {join}$ By now, the Haskell translations should be hopefully self-explanatory:

1. join . fmap join = join . join
2. join . fmap return = join . return = id
3. return . f = fmap f . return
4. join . fmap (fmap f) = fmap f . join

(Remember that fmap is the part of a functor that acts on morphisms.) These laws seem a bit impenetrable at first, though. What on earth do these laws mean, and why should they be true for monads? Let’s explore the laws.

### The first law

join . fmap join = join . join A demonstration of the first law for lists. Remember that join is concat and fmap is map in the list monad.

In order to understand this law, we'll first use the example of lists. The first law mentions two functions, join . fmap join (the left-hand side) and join . join (the right-hand side). What will the types of these functions be? Remembering that join’s type is [[a]] -> [a] (we’re talking just about lists for now), the types are both [[[a]]] -> [a] (the fact that they’re the same is handy; after all, we’re trying to show they’re completely the same function!). So we have a list of lists of lists. The left-hand side, then, performs fmap join on this 3-layered list, then uses join on the result. fmap is just the familiar map for lists, so we first map across each of the list of lists inside the top-level list, concatenating them down into a list each. So afterward, we have a list of lists, which we then run through join. In summary, we 'enter' the top level, collapse the second and third levels down, then collapse this new level with the top level.

What about the right-hand side? We first run join on our list of list of lists. Although this is three layers, and you normally apply a two-layered list to join, this will still work, because a [[[a]]] is just [[b]], where b = [a], so in a sense, a three-layered list is just a two layered list, but rather than the last layer being 'flat', it is composed of another list. So if we apply our list of lists (of lists) to join, it will flatten those outer two layers into one. As the second layer wasn't flat but instead contained a third layer, we will still end up with a list of lists, which the other join flattens. Summing up, the left-hand side will flatten the inner two layers into a new layer, then flatten this with the outermost layer. The right-hand side will flatten the outer two layers, then flatten this with the innermost layer. These two operations should be equivalent. It’s sort of like a law of associativity for join.

Maybe is also a monad, with

return :: a -> Maybe a
return x = Just x

join :: Maybe (Maybe a) -> Maybe a
join Nothing         = Nothing
join (Just Nothing)  = Nothing
join (Just (Just x)) = Just x


So if we had a three-layered Maybe (i.e., it could be Nothing, Just Nothing, Just (Just Nothing) or Just (Just (Just x))), the first law says that collapsing the inner two layers first, then that with the outer layer is exactly the same as collapsing the outer layers first, then that with the innermost layer.

Exercises
Verify that the list and Maybe monads do in fact obey this law with some examples to see precisely how the layer flattening works.

### The second law

join . fmap return = join . return = id

What about the second law, then? Again, we'll start with the example of lists. Both functions mentioned in the second law are functions [a] -> [a]. The left-hand side expresses a function that maps over the list, turning each element x into its singleton list [x], so that at the end we’re left with a list of singleton lists. This two-layered list is flattened down into a single-layer list again using the join. The right hand side, however, takes the entire list [x, y, z, ...], turns it into the singleton list of lists [[x, y, z, ...]], then flattens the two layers down into one again. This law is less obvious to state quickly, but it essentially says that applying return to a monadic value, then joining the result should have the same effect whether you perform the return from inside the top layer or from outside it.

Exercises
Prove this second law for the Maybe monad.

### The third and fourth laws

return . f = fmap f . return

join . fmap (fmap f) = fmap f . join

The last two laws express more self-evident facts about how we expect monads to behave. The easiest way to see how they are true is to expand them to use the expanded form:

1. \x -> return (f x) = \x -> fmap f (return x)
2. \x -> join (fmap (fmap f) x) = \x -> fmap f (join x)
Exercises
Convince yourself that these laws should hold true for any monad by exploring what they mean, in a similar style to how we explained the first and second laws.

### Application to do-blocks

Well, we have intuitive statements about the laws that a monad must support, but why is that important? The answer becomes obvious when we consider do-blocks. Recall that a do-block is just syntactic sugar for a combination of statements involving (>>=) as witnessed by the usual translation:

do { x }                 -->  x
do { let { y = v }; x }  -->  let y = v in do { x }
do { v <- y; x }         -->  y >>= \v -> do { x }
do { y; x }              -->  y >>= \_ -> do { x }


Also notice that we can prove what are normally quoted as the monad laws using return and (>>=) from our above laws (the proofs are a little heavy in some cases, feel free to skip them if you want to):

1. return x >>= f = f x. Proof:
   return x >>= f
= join (fmap f (return x)) -- By the definition of (>>=)
= join (return (f x))      -- By law 3
= (join . return) (f x)
= id (f x)                 -- By law 2
= f x

2. m >>= return = m. Proof:
   m >>= return
= join (fmap return m)    -- By the definition of (>>=)
= (join . fmap return) m
= id m                    -- By law 2
= m

3. (m >>= f) >>= g = m >>= (\x -> f x >>= g). Proof (recall that fmap f . fmap g = fmap (f . g)):
   (m >>= f) >>= g
= (join (fmap f m)) >>= g                          -- By the definition of (>>=)
= join (fmap g (join (fmap f m)))                  -- By the definition of (>>=)
= (join . fmap g) (join (fmap f m))
= (join . fmap g . join) (fmap f m)
= (join . join . fmap (fmap g)) (fmap f m)         -- By law 4
= (join . join . fmap (fmap g) . fmap f) m
= (join . join . fmap (fmap g . f)) m              -- By the distributive law of functors
= (join . join . fmap (\x -> fmap g (f x))) m
= (join . fmap join . fmap (\x -> fmap g (f x))) m -- By law 1
= (join . fmap (join . (\x -> fmap g (f x)))) m    -- By the distributive law of functors
= (join . fmap (\x -> join (fmap g (f x)))) m
= (join . fmap (\x -> f x >>= g)) m                -- By the definition of (>>=)
= join (fmap (\x -> f x >>= g) m)
= m >>= (\x -> f x >>= g)                          -- By the definition of (>>=)


These new monad laws, using return and (>>=), can be translated into do-block notation.

Points-free style Do-block style
return x >>= f = f x do { v <- return x; f v } = do { f x }
m >>= return = m do { v <- m; return v } = do { m }
(m >>= f) >>= g = m >>= (\x -> f x >>= g)
   do { y <- do { x <- m; f x };
g y }
=
do { x <- m;
y <- f x;
g y }


The monad laws are now common-sense statements about how do-blocks should function. If one of these laws were invalidated, users would become confused, as you couldn't be able to manipulate things within the do-blocks as would be expected. The monad laws are, in essence, usability guidelines.

Exercises

In fact, the two versions of the laws we gave:

-- Categorical:
join . fmap join = join . join
join . fmap return = join . return = id
return . f = fmap f . return
join . fmap (fmap f) = fmap f . join

-- Functional:
m >>= return = m
return m >>= f = f m
(m >>= f) >>= g = m >>= (\x -> f x >>= g)


are entirely equivalent. We showed that we can recover the functional laws from the categorical ones. Go the other way; show that starting from the functional laws, the categorical laws hold. It may be useful to remember the following definitions:

join m = m >>= id
fmap f m = m >>= return . f

Thanks to Yitzchak Gale for suggesting this exercise.

## Summary

We've come a long way in this chapter. We've looked at what categories are and how they apply to Haskell. We've introduced the basic concepts of category theory including functors, as well as some more advanced topics like monads, and seen how they're crucial to idiomatic Haskell. We haven't covered some of the basic category theory that wasn't needed for our aims, like natural transformations, but have instead provided an intuitive feel for the categorical grounding behind Haskell's structures.